Effects of heating rate during solid-solution treatment on microstructure and fatigue properties of AA2524 T3 Al–Cu–Mg sheet. (15th August 2016) - Shen, Fanghua; Wang, Bin; Yi, Danqing; Liu, Huiqun; Tang, Cong; Shou, Wenbin
Abstract: T3 AA2524 (Al–Cu–Mg) aluminum alloy sheets were fabricated using two different heating rates (air furnace and salt bath) during the solid-solution treatment. The corresponding microstructure, recrystallization mechanisms, and fatigue behavior were investigated by means of transmission electron microscopy, scanning electron microscopy, electron back scattering diffraction, and optical microscopy. The results showed that the heating rate had a significant effect on the microstructure, owing to the different recrystallization mechanisms induced, namely, strain-induced boundary migration and particle-stimulated nucleation. Elongated fibrous grains (approximately 75 μm) with Cube, Goss, and S orientations were obtained for low heating rate, while fine equiaxed grains structure (approximately 13 μm) with a P-type orientation were obtained for high heating rate. The rate of fatigue crack growth in the case of former was lower than that in the latter during the stable stage. The effects of crack closure, induced by the large grain size and a high Schmid factor, would be responsible for such difference in fatigue property. Graphical abstract: Highlights: The effects of heating rate on microstructure in 2524 T3 alloy sheet were studied. Schematic models were built to explain such difference in microstructure. Corresponding fatigue properties and mechanisms were studied.